Does external beam radiation therapy to the pelvis portend worse ileal pouch outcomes? An international multi‐institution collaborative study. (1st December 2018) - Lightner, A. L.; Spinelli, A.; McKenna, N. P.; Hallemeier, C. L.; Fleshner, P.
Abstract: Aim: Short‐term morbidity and long‐term functional outcome of patients with an ileal pouch‐anal anastomosis (IPAA) exposed to pelvic external beam radiation therapy (EBRT) remains unknown. We report the largest series to date regarding the effects of pelvic EBRT on: (i) 30‐day postoperative outcomes; and (ii) long‐term functional outcome following IPAA. Method: A retrospective chart review was conducted of patients who received EBRT before or after IPAA between 1980 and 2017 across three international inflammatory bowel disease referral centres. Results: Nineteen patients were included. Indications for EBRT were rectal adenocarcinoma ( n  = 13), prostate adenocarcinoma ( n  = 4) or anal squamous cell carcinoma (ASCC) ( n  = 2). EBRT was given prior to IPAA in 12 (63%) patients and after IPAA in seven (37%). In EBRT before IPAA, patients had a median of 5 (range: 4–8) daytime bowel movements, 1 (range: 0–5) night‐time bowel movement, no daytime incontinence, and only one patient used pads at a median follow up of 25 (range: 11–163) months; one patient underwent pouch excision 15 months after IPAA. In EBRT after IPAA, patients reported a median of 8 (range: 5–10) daytime and 2 (range: 0–5) night‐time bowel movements, 80% had either daytime or night‐time incontinence and 80% used pads at a median follow up of 90 (range: 25–315) months. Conclusion: Pelvic EBRT administered prior to IPAA is associated with acceptable long‐term function outcome. However, when pelvic EBRT is given to an IPAA in situ, most patients experience poor long‐term pouch function without pouch failure.